The impact of digital transformation and the use of Whatsapp chatbot technology on the development of the creative economy in Deli district of Serdang - Nasution, Anisah Salsabila; Nurbaiti, Nurbaiti; Harahap, Rahmat Daim (Universitas Ibn Khladun Bogor, 2023)
In our current revolutionary era, the digital economy is a projection of new talent that can inspire competitiveness. The digital economy is currently growing rapidly around the world, including Indonesia, as evidenced by the increasing number of internet users. However, it is becoming increasingly clear that ongoing digitization is not only benefiting those economic actors who can thrive with technological advances, but also creating inequalities for those who cannot keep up. The purpose of this study was to determine the effect of digital transformation and the use of whatsapp chatbot technology on the development of the creative economy in Deli Serdang district. The type of research used in this research is quantitative research. The data source used is primary data by distributing questionnaires to respondents, in this case, creative economy actors in Deli Serdang district. The analysis technique used in this study is multiple linear regression analysis using the SPSS 26 program. The results of the study state that the digital transformation and whatsapp chatbot variables have a positive and significant effect on the creative economy